Role of Travel Motivation and Destination Image to Promote Destination Loyalty - Abbas, Muhammad; Hussain, Kashif; Bajwa, Sami Ullah; Rasheed, Muhammad Athar; Yaghmour, Samer (Academica Turistica - Tourism and Innovation Journal, 2025)
This study examines the impact of travel motivation on destination loyalty through the mediating role of destination image and moderating influence of destination satisfaction using the push and pull theory. The data was collected from 209 local visitors visiting Kaghan Valley, the northern areas of Pakistan, through a self-administered questionnaire. Partial Least Squares Structural Equation Modeling was employed to investigate the impact of hypotheses. Results postulate that there is a positive influence of travel motivation on destination loyalty whereas destination image significantly mediates this relationship. Results further reveal an insignificant moderating influence of destination satisfaction on destination image and destination loyalty. This research provides guidelines for the policymakers to adopt destination-specific strategies to boost tourism industry in Pakistan. Keywords: travel motivation, destination image, destination satisfaction, destination loyalty, Pakistan.